Advances in Human Factors in Cybersecurity Proceedings of the AHFE 2018 International Conference on Human Factors in Cybersecurity, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Ahram, Tareq Z.; Nicholson, Denise; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book reports on the latest research and developments in the field of cybersecurity, particularly focusing on personal security and new methods for reducing human error and increasing cyber awareness, as well as innovative solutions for increasing the security of advanced Information Technology (IT) infrastructures. It covers a broad range of topics, including methods for human training; novel cyber-physical and process-control systems; social, economic, and behavioral aspects of cyberspace; issues concerning the cybersecurity index; security metrics for enterprises; and risk evaluation. Based on the AHFE 2018 International Conference on Human Factors in Cybersecurity, held on July 21-25, 2018, in Orlando, Florida, USA, the book not only presents innovative cybersecurity technologies, but also discusses emerging threats, current gaps in the available systems, and future challenges that can be successfully overcome with the help of human factors research.
Keywords: Computational intelligence; Data protection; User interfaces (Computer systems).; Human-computer interaction; Information technology -- Management; Computer crimes; Computational Intelligence; Data and Information Security; User Interfaces and Human Computer Interaction; Business IT Infrastructure; Cybercrime